EVALUASI BERBASIS TEKNOLOGI E-ASESSMEN, CBT, APLIKASI DIGITAL - Halimah Syutri; Julhadi Julhadi (Ensiklopedia of Journal, 2026)
The rapid development of information technology has changed the educational paradigm, including the learning evaluation process, where conventional paper-based evaluations are considered inefficient, slow in providing feedback, and prone to errors or accidents. Therefore, the implementation of technology-based evaluations, such as E-Assessment, Computer-Based Testing (CBT), and digital applications, is an alternative strategy to increase the effectiveness, accuracy, and relevance of assessments. National research uses qualitative descriptive methods based on literature studies, by analyzing literature from scientific journals, educational books, policy guidelines, and research related to the implementation of digital evaluation, to map the benefits, challenges, and best practices in the context of formal education. The results of the study indicate that Technology-based evaluation can improve the accuracy of student competency measurements, accelerate data processing, and provide instant feedback that supports continuous learning. Furthermore, this technology increases learning motivation, reduces the potential for cheating, and facilitates systematic monitoring of learning outcomes. However, implementing digital evaluation faces challenges such as infrastructure readiness, teacher and student digital literacy, and data security. Therefore, its successful use requires support from training, policies, and sound system integration.Keywords: Technology-based evaluation, E-Assessment, CBT, Digital applications, Modern education